Effect of the external magnetic field on the dynamics and power of the self-sustained plasma-beam discharge - Hrechko, Ya.O.; Azarenkov, N.A.; Babenko, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Boloto, D.A.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2018)
The paper is related to the studying the effect of the external constant magnetic field on the dynamics and power of the self-sustained plasma-beam discharge. It is shown that a relatively small (up to 1 kG) magnetic field of a specific configuration allows to increase the power inputted into the discharge at several times. The distinctive features of the discharge in the presence of the external constant magnetic field are noted. Робота пов’язана з дослідженням впливу зовнішнього постійного магнітного поля на динаміку і потужність самостійного плазмово-пучкового розряду. Показано, що відносно невелике (до 1 кГс) магнітне поле специфічної конфігурації дозволяє в декілька разів збільшити потужність, що вводиться в розряд. Відзначено відмінні особливості протікання розряду при наявності зовнішнього постійного магнітного поля. Работа связана с исследованием влияния внешнего постоянного магнитного поля на динамику и мощность самостоятельного плазменно-пучкового разряда. Показано, что относительно небольшое (до 1 кГс) магнитное поле специфической конфигурации позволяет в несколько раз увеличить вводимую в разряд мощность. Отмечены отличительные особенности протекания разряда при наличии внешнего постоянного магнитного поля.